Proximate composition of two puffer fish species, Leiodon cutcutia and Dichotomyctere fluviatilis of Bangladesh - Chowdhury, Ishtiak Ahmed; Hasan, Md Rakibul; Parveen, Suraiya; Dey, Shuvra Kanti; Billah, Md Baki (Jahangirnagar University Journal of Biological Sciences, 2019)
Protein, lipid, ash and moisture content in the body muscles of two commonly available puffer fish species in Bangladesh (Leiodon cutcutia and Dichtomyctere fluviatilis) have been analysed from January 2018 to June, 2018. The puffer fish species were collected from different habitats i.e., Leiodon cutcutia from freshwater and Dichtomyctere fluviatilis from estuarine water. The percentage of the proximate composition varied in different months in both the species. In Leiodon cutcutia, moisture content fluctuated from 79.32% to 87.61% with an average of 83.75%; protein content from 6.35% to 13.31% with an average of 9.49%; lipid content from 1.57% to 2.32% with an average of 1.92% and ash content from 2.30% to 3.27% with an average of 2.84%. In Dichotomyctere fluviatilis, moisture content fluctuated from 73.77% to 84.18% with an average of 77.49%; protein content from 10.03% to 19.77% with an average of 16.80%; lipid content from 0.92% to 1.71% with an average of 1.32% and ash content from 2.77% to 3.34% with an average of 3.05%. The comparative evaluation of the nutritional value of the studied fish species revealed that the puffer fish from estuarine environment might contain higher amount of nutrients. Thus, proper utilization of this species towards sustainable management, nutritional composition and biosecurity issues will lead to achieve sustainable blue economy. Jahangirnagar University J. Biol. Sci. 8(1): 25-33, 2019 (June)